Analysis Of The Implementation Of The National Health Insurance Standard Inpatient Class Program (KRIS) At Grandmed Hospital Lubuk Pakam - Br.Tarigan, Maria haryanti; Rahmadani Sitepu; Novita Br Ginting Munthe (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: The Standard Inpatient Class (KRIS) Program in the National Health Insurance (JKN) aims to ensure fair and equitable health services for all BPJS Kesehatan participants. The implementation of KRIS still requires readiness of facilities and infrastructure in accordance with the standards set by the government. In terms of planning. Objective: to analyze the implementation of the KRIS program carried out at Grandmed Lubuk Pakam Hospital. The type of research used is qualitative research with a case study approach that focuses on collecting information. Research method: The type of research used is qualitative research with a case study approach that focuses on collecting information. This research will be conducted at Grandmed Lubuk Pakam Hospital located on Jalan Raya Medan-Lubuk Pakam. The triangulation method used is method triangulation involving several key informants and triangulation. The results of this interview provide important insights that not only strengthen observational data, but also help formulate recommendations to improve the implementation of KRIS in hospitals. The informants in this study were the Head of Hospital, Staff, and patients at Grandmed Lubuk Pakam Hospital. The results of the study indicate that improvements are still needed in various lines to fulfill the implementation of KRIS so that patients get maximum service. Input components, including human resources, funds and infrastructure in the implementation of the National Health Insurance Standard Inpatient Class (KRIS) program at Grandmed Lubuk Pakam Hospital have been provided, but staff qualifications according to their scientific fields are still not met. Nursing and professional qualifications are expected to fulfill the work section. Process components, including policies implemented, recording and reporting, monitoring, inspection and assessment of the implementation of the National Health Insurance Standard Inpatient Class (KRIS) program at Grandmed Lubuk Pakam Hospital have been implemented and evaluated. Conclusion: there are still some that have not been implemented related to the timeliness of implementation. Output components, including the coverage figures for the implementation of the National Health Insurance Standard Inpatient Class (KRIS) program have met health requirements. However, the monitoring commitment must still be maintained and improved.